RELATIONSHIP BETWEEN ACADEMIC STRESS AND ACADEMIC PERFORMANCE AMONG UNDERGRADUATE NURSING STUDENTS (The Research of Medical Science Review, 2025)
Background: Academic stress is a prevalent issue among nursing students due to the rigorous academic and clinical demands of their training. This stress can negatively influence students' academic performance, emotional well-being, and long-term professional development. Understanding this relationship is essential for improving student support and outcomes in nursing education.Aim: This study aimed to examine the relationship between academic stress and academic performance among undergraduate nursing students.Methods: A descriptive correlational study was conducted among 260 undergraduate nursing students selected from various nursing colleges in Swat, Pakistan. The sample size was calculated using the Raosoft calculator with a total population of 700. A validated self-administered questionnaire was used to assess stress levels (using a standardized academic stress scale), and academic performance was measured using students’ self-reported GPA. Data were analyzed using SPSS version 27, with descriptive statistics and Pearson correlation tests used to assess associations.Results: The mean academic stress score was 67.4 (SD = 13.2), with 50.8% of students experiencing moderate stress and 30.8% reporting high stress. The mean GPA was 3.13 (SD = 0.42). A significant negative correlation was found between academic stress and GPA (r = -0.421, p < 0.001), indicating that higher stress levels were associated with lower academic performance.Conclusion: The findings highlight a strong inverse relationship between academic stress and academic performance. Nursing institutions must implement stress-reduction strategies and provide academic and emotional support to optimize student outcomes.